The Relationship Between Family Support and Depression among Patient with Renal Failure Patients - Rahmawati Maulidia; Achmad Dafir Firdaus; Retno Ayu Wulandari (The Journal of Palembang Nursing Studies, 2022)
Background: Family support is an essential factor supporting psychological conditions during hemodialysis. Purpose: We analyzed the relationship between family support and depression in kidney failure patients undergoing hemodialysis in Hemodialysis Room Dr. Saiful Anwar Hospital Malang Methods: A cross-sectional study was used. Sample selection technique determined by quota sampling method then 107 patients were obtained as participants. Data were collected using MOS-Social Support Survey (MOS-SSS) & Zung Self-Rating Depression Scale (ZSDS) questionnaire. Data analysis used the Spearman Rho test with ? = 0.05. Results: Data showed that 48 respondents (44.9%) had sufficient family support. Most of the respondents, 46 respondents (43%), experienced mild depression. The statistical test showed a significant relationship between family support and depression with p < 0.001. Relationship strength value (r) is -0.530 or negative, and family support is inversely related to the incidence of depression. The correlation strength category is vital. Conclusions: There is a significant relationship between family support and depression in patients with kidney failure in Hemodialysis Room Dr. Saiful Anwar Hospital. The study suggests that the nurse provides family education to encourage positive family support.